The effect of fitness level on cardiac autonomic regulation, IL-6, total antioxidant capacity, and muscle damage responses to a single bout of high-intensity interval training - Cipryan, Lukas (Journal of sport and health science, 2018)
PURPOSE: The aim of this study was to investigate the influence of the cardiorespiratory fitness level on the response to high-intensity interval training (HIIT) with an individually adjusted running speed of the same relative intensity. The evaluation focused on acute cardiorespiratory response, postexercise cardiac autonomic modulation (heart rate variability (HRV)) and biochemical markers of inflammation, oxidative stress, and muscle damage. METHODS: Thirty participants were divided into 3 subgroups: well trained, moderately trained, and untrained. All the participants performed 30 min HIIT composed of 6 × 2 min interval exercise with work-to-relief ratio = 1 and work intensity 100% of individual velocity at maximal oxygen consumption (VO2​max ). Acute cardiorespiratory variables, postexercise HRV, lactate, interleukin-6 (IL-6), total antioxidant capacity (TAC), creatine kinase, and myoglobin up to 4 h after HIIT were monitored. RESULTS: The differences in relatively expressed cardiorespiratory variables (heart rate, VO2) during HIIT were at most moderate, with the most pronounced between-group differences in absolute VO2 values. The disruption of the postexercise HRV was the most pronounced in untrained individuals, and this difference persisted 1 h after HIIT. The highest postexercise IL-6 and TAC concentrations and the lowest changes in creatine kinase and myoglobin were revealed in well-trained individuals. CONCLUSION: The higher fitness level was associated with the less pronounced postexercise cardiac autonomic changes and their faster restoration, even when there were similar acute cardiorespiratory responses. These findings were simultaneously accompanied by the higher postexercise IL-6 and TAC concentrations and less significant changes in muscle damage biochemical markers in well-trained individuals.
Keywords: Creatine kinase; Total antioxidant capacity; Training status; Heart rate variability; Myoglobin; Inflammation